Main aspects of MEDISAN's scientific and editorial production in the five-year period 2017-2021 - Esther Mayor Guerra; Giselle Velez Fernández; Delfina Durán Rengifo; Sara Riccis Salas Palacios (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: In the academic world, scientific publication has become a constant problem, both in its quantitative and qualitative elements. Objective: To characterize MEDISAN's publication rate according to some aspects of its scientific and editorial production. Methods: An observational, descriptive and transversal research, of bibliometric type, was carried out on the scientific production of MEDISAN journal from Santiago de Cuba during the five-year period 2017-2021. The study population was made up of all scientific articles published in that period according to the records of SciELO Citation Index and Google Scholar databases, as well as those of the journal itself on the Open Journal Systems. Results: During the analyzed period, 38 issues were published, which included 679 articles and 2,367 authors. The year 2017 stood out with the highest number of publications (31.8%) and the year 2019 with a lower number (14.3%). Cuban authors had the greatest contribution (629 articles), especially those from Santiago de Cuba province, where professionals from University of Medical Sciences stood out, with 50.1% of all production. The h5 index revealed a trend of increasing citations received by the journal, since in 2021 it was 23 and in 2022 it increased to 27. Conclusions: The analysis of scientific and editorial production revealed the strengths and weaknesses of the journal, which makes it possible to draw up policies to increase its quality and, with it, its visibility in databases.